THE CREDITWORTHINESS ASSESSMENT OF THE CONSTRUCTION ORGANIZATIONS - Anton Murzin; Tatiana Rogova (Вестник Северо-Кавказского федерального университета)
The following article gives the information about the researches of the solvency analysis problem of economical entities. This problem belongs to special types of the enterprises, namely construction organizations which financial and economic activity is characterized by branch specifics. During the research shortcomings of the existing assessment practice of the borrowers solvency were reveled: the practice was directed mainly to the credit institutions personal interests satisfaction. As the result, the author’s concept of an advanced solvency assessment technique, which considered branch features of construction borrowers, has been offered.